The Application Of The Stad Type Cooperative Model In Enhancing Faith Learning Outcomes To The Final Day Of Class VI Students Of Upt SDN 03 Asam Jujuhan - Zulkadri, Zulkadri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The research is attracted by students' difficulties in mastering basic competencies about being intelligent until the end of the day. This can be seen in the lack of ability to mention the names of the Last Days and explain the signs of the Last Days, students also have difficulty understanding the phases that humans go through on the Last Days, because this material is clearly abstract material and material about the Last Days. also less interesting for students, because they also often hear the same material in MDA lessons and religious lectures. This study aims to determine the application of the STAD type cooperative model in improving faith learning outcomes until the end of the day in class VI students of UPT SDN 03 Asam Jujuhan. The purpose of this study was to apply the STAD type cooperative model in improving the learning outcomes of Faith in the Last Day in class VI students of UPT SDN 03 Asam Jujuhan. This research method is a type of classroom action research (CAR) in the form of recycling, namely: planning, action or implementation of action, observation and reflection, carried out in two cycles and the target of this research was class VI students of UPT SDN 03 Asam Jujuhan. The results of this study are that the application of the STAD type cooperative learning model can improve student learning outcomes at UPT SDN 03 Asam Jujuhan for the 2021/2022 school year, from the results of the formative tests and observation sheets of teaching and learning activities have increased from cycle I to cycle III, namely (57,69 %) and cycle II (76.92%) so that this learning model can be used as an alternative to learning Islamic Religious Education in Elementary Schools.